Wiley Encyclopedia of Biomedical Engineering 2006
DOI: 10.1002/9780471740360.ebs0306
|View full text |Cite
|
Sign up to set email alerts
|

Muscle Fiber Conduction Velocity

Abstract: The speed with which an action potential (AP), or excitatory impulse, travels along the membrane of a skeletal muscle fiber is known as its conduction velocity (CV). Muscle fiber CV may be estimated from the electromyogram (EMG) and can be used as a sensitive measure of the excitability of the muscle fiber membrane in addition to being related to the type, diameter, rate of activation, temperature, and physiological or pathological state of the muscle fiber. Conduction velocity estimates are frequently used as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 74 publications
1
8
0
Order By: Relevance
“…The EMG activity showed that the onset latency of the anterior digastric muscle in the experimental group was significantly delayed than in the control group, but there was no significant difference among ages in either the control or the experimental group. Measuring the onset latency is the best way to assess the muscle fiber conduction velocity during stimulation (Beck, 2006). In stimulated muscle contractions in rats, the latency was delayed at 3 weeks of age, however, the delay in latency disappeared from 5 weeks of age onwards (Seki et al, 2002;Changsiripun et al, 2012).…”
Section: Growth-related Changes and Effects Of Low Occlusal Loading On Muscular Workmentioning
confidence: 99%
“…The EMG activity showed that the onset latency of the anterior digastric muscle in the experimental group was significantly delayed than in the control group, but there was no significant difference among ages in either the control or the experimental group. Measuring the onset latency is the best way to assess the muscle fiber conduction velocity during stimulation (Beck, 2006). In stimulated muscle contractions in rats, the latency was delayed at 3 weeks of age, however, the delay in latency disappeared from 5 weeks of age onwards (Seki et al, 2002;Changsiripun et al, 2012).…”
Section: Growth-related Changes and Effects Of Low Occlusal Loading On Muscular Workmentioning
confidence: 99%
“…Conduction velocity (CV): The speed which an action potential travels along the membrane of a skeletal muscle fiber [ 68 ]. The estimation of the conduction velocity was calculated using the techniques described by Farina et al [ 69 , 70 ], which use a maximum likelihood multiple-channel method, using the Newton method for efficient optimization.…”
Section: Methodsmentioning
confidence: 99%
“…Motor unit action potentials (MUAPs) originate near the middle of the muscle, at the neuromuscular junctions of their Aα motor neurons, and propagate in each direction toward the bones to which the muscle is attached. The combined field generated by all activated motor units is the CMAP which can be observed from electrodes placed in close proximity to the muscle ( Beck, 2006 ).…”
Section: Methodsmentioning
confidence: 99%